2006
DOI: 10.1207/s15324826an1303_3
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Visual Hallucinations: An Analysis of Affective Valence

Abstract: Visual formaesthesias (hallucinations) are a common symptom of neurological insult. Research on emotional valances and the laterality of emotional valence extends to clinical populations experiencing visual hallucinations. The purpose of this project was to evaluate the relationship of reported hemispace of visual formaesthesia and associated emotional valence. Based on current literature exploring asymmetries in the processing of emotional valence, it was predicted that right visual formaesthesias would be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Thus, the fact that only patients with right-side lesions reported visual hallucinations suggests an effect of the lesion side on the occurrence of hallucinatory phenomena. Thus, we propose that the side of the occipital lesion determines the occurrence of visual hallucinations whereas the visual field of apparition influences the emotional valence, with more frequent hallucinations in the blind, contralesional visual field than in the ipsilesional visual field, as reported in the previously cited study by Walters et al (2006) Regardless, further studies are necessary to elucidate the link between the lesion side, the visual field of apparition and the various parameters of visual hallucinations (nature, frequency, severity, similarity with mental imagery, emotional valence, etc.). Interestingly, preliminary results from one of our group’s current studies using the Q3H questionnaire suggest that the occurrence and type of visual hallucinations in hemianopic patients might also depend on the extent of the lesion.…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionssupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, the fact that only patients with right-side lesions reported visual hallucinations suggests an effect of the lesion side on the occurrence of hallucinatory phenomena. Thus, we propose that the side of the occipital lesion determines the occurrence of visual hallucinations whereas the visual field of apparition influences the emotional valence, with more frequent hallucinations in the blind, contralesional visual field than in the ipsilesional visual field, as reported in the previously cited study by Walters et al (2006) Regardless, further studies are necessary to elucidate the link between the lesion side, the visual field of apparition and the various parameters of visual hallucinations (nature, frequency, severity, similarity with mental imagery, emotional valence, etc.). Interestingly, preliminary results from one of our group’s current studies using the Q3H questionnaire suggest that the occurrence and type of visual hallucinations in hemianopic patients might also depend on the extent of the lesion.…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionssupporting
confidence: 63%
“…Over the past 5 years, our group and others have suggested that the side of the occipital lesion might be an important factor in the nature and severity of visual impairments in hemianopic patients. Similarly, Walters et al (2006) investigated whether complex visual hallucinations caused by an occipital lesion might be linked to the lesion side and to patients’ emotional valence. In their study, they systematically searched for hallucinations in left or right brain-damaged patients and recorded the side of the hallucination, as well as its emotional valence.…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionsmentioning
confidence: 99%
“…1. Prefrontal cortex in the right cerebral hemisphere is dominant in depressed mood and withdrawal-related emotion (van Honk & Schutter, 2006;Walters, Harrison, Williamson, & Foster, 2006;Herrington, Heller, Engels, Baniach, Webb, & Miller, 2010). Left prefrontal cortex has an analogous role with respect to positive, approach-oriented emotion.…”
Section: Demons and The Alien Handmentioning
confidence: 99%
“…Spatial coordinates continue to have moral or at least emotional meanings at the present time (seeWalters, Harrison, Williamson, & Foster, 2006;Tamagni, Mantei, & Brugger, 2009).…”
mentioning
confidence: 99%
“…As a rule, damage to (anterior) regions of the LH induces negative affect, depression or even elicits "catastrophic reactions", while comparable damage to the right hemisphere may rather lead to enhanced positive mood, anosodiaphoria (i.e., marked downplaying of the consequences of an illness) and mania-like, euphoric reactions (Davidson, 1995;Gainotti, 1972;Silberman and Weingartner, 1986). Also, unilateral hallucinations after brain damage are experienced as emotionally negative when occurring in the left visual field (LVF), while those in the right visual field (RVF) are of predominantly positive content (Walters et al, 2006;Mollet et al, 2007). Even in not strictly lateralized psychiatric disorders, the degree of negativity of hallucinatory experiences correlates with specifically RH involvement, both in the auditoryverbal (Sommer et al, 2008) and somesthetic domain (Brugger, 2007).…”
mentioning
confidence: 99%